2022
DOI: 10.1109/tse.2021.3107680
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Analysis for Cyber-Physical Systems: Scalable Solutions and Results in the Space Domain

Abstract: On-board embedded software developed for spaceflight systems (space software) must adhere to stringent software quality assurance procedures. For example, verification and validation activities are typically performed and assessed by third party organizations. To further minimize the risk of human mistakes, space agencies, such as the European Space Agency (ESA), are looking for automated solutions for the assessment of software testing activities, which play a crucial role in this context. Though space softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 106 publications
(193 reference statements)
0
15
0
Order By: Relevance
“…Indeed, in the worst case (i.e., ESAIL-ADCS), mutation analysis can be performed in 9 hours with 100 parallel computation nodes; in safety-critical contexts, where development entails large costs, buying computation time on the Cloud is affordable. Code-driven mutation analysis for systems with similar characteristics lasts considerably more [56], [57]. For ESAIL and LIBP, for example, mutants sampling 6 makes code-driven mutation analysis feasible with parallel computation nodes, leading to 1800 hours (ESAIL) and 3 hours (LIBP) of execution time, which is still significantly higher than the time required by DaMAT.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, in the worst case (i.e., ESAIL-ADCS), mutation analysis can be performed in 9 hours with 100 parallel computation nodes; in safety-critical contexts, where development entails large costs, buying computation time on the Cloud is affordable. Code-driven mutation analysis for systems with similar characteristics lasts considerably more [56], [57]. For ESAIL and LIBP, for example, mutants sampling 6 makes code-driven mutation analysis feasible with parallel computation nodes, leading to 1800 hours (ESAIL) and 3 hours (LIBP) of execution time, which is still significantly higher than the time required by DaMAT.…”
Section: Resultsmentioning
confidence: 99%
“…Mutants sampling consists of selecting a subset of mutants to compute the mutation score [58]. In our previous work [57], we have demonstrated that a fixed-width sequential confidence interval approach guarantees the accurate estimation of the mutation score. ever, although useful to derive an accurate mutation score, mutants sampling prevents the complete identification of test suite shortcomings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations